Analysis and Design of Web-Based Billing Information System at the Employee Cooperative of PT. Spindo Karawang Factory - Anggi Elanda; Rahmat Gunawan; M. Wahidin; Budhi Santoso (Dirgamaya: Jurnal Manajemen dan Sistem Informasi, 2021)
In the digital era, people often call the era of the industrial revolution 4.0 demanding speed and accuracy in all fields. Moreover, the speed and accuracy in delivering and receiving information for decision making so as not to compete with competitors. The presentation of information is not only fast, accurate, it must also be easily understood by the person receiving the information. One business entity that must also take advantage of this technological development is a cooperative. In the cooperative PT. Spindo Karawang Factory transaction activities still have to be processed in Microsoft Excel, so that data duplication or inconsistency often occurs, data updates are not updated, there is no data backup and data that has not been integrated with other systems. The purpose of this research is to increase the effectiveness and efficiency of the transaction process in the cooperative. The research method used in this research is the System Development Life Cycle (SDLC) with the waterfall approach. The result of this research is the cooperative invoice information system of PT. Spindo Karawang Factory is web-based which is expected to be able to improve the process in the cooperative to be more effective and efficient.